Aspectos biológicos de Dione juno juno (Cramer) (Lepidoptera: Nymphalidae) em genótipos de maracujazeiro - Boiça Júnior, Arlindo Leal; Angelini, Marina Robles; Oliveira, João Carlos de (FapUNIFESP (SciELO), 2008)
It was studied the effect of passion fruit genotypes on Dione juno juno (Cramer) (Lepidoptera: Nymphalidae) development. The experiment was carried out in a laboratory, under controlled conditions (temperature: 26 ± 1° C, RH = 60 ± 10% and photophase of 14 hours). Newly-hatched larvae were fed with leaves from different passion fruit genotypes: Passiflora edulis Sims., P. alata Dryand., P. serrato-digitata L., P. edulis f. flavicarpa Deg. ('Sul Brasil'), P. edulis f. flavicarpa, P. edulis f. flavicarpa ('Maguary FB-100') and P. foetida L. Fifty larvae from eggs collected in the field were used per genotype. Larvae were kept on passion fruits branches inside PVC tubes until pupation. Daily observations were performed and branches were replaced whenever necessary. The following parameters were evaluated: duration and viability of larval and pupal phases, larval and pupal weight and adult longevity. The experiment was arranged in randomized blocks design with seven treatments and ten replications. Data were subjected to an ANOVA and means were compared by Tukey test at 5% of probability. The least adequate genotypes for D. juno juno development were P. alata, P. serrato-digitata and P. foetida, showing a high level of antibiosis, while P. edulis, P. edulis f. flavicarpa, 'Maguary FB-100' and 'Sul Brasil' were the most suitable.
Biological aspects of Dione juno juno (Cramer) (Lepidoptera: Nymphalidae) on passion fruit genotypes
Keywords: Antibiosis; Passiflora sp.; Passion fruit caterpillar; Dione juno; Lepidoptera; Nymphalidae; Passiflora; Passiflora alata; Passiflora edulis; Passiflora edulis f. flavicarpa; Passiflora foetida